Hemato-Biochemical Analyses of Lactating Cross-Bred Jersey Cattle at Kaski District, Nepal - Regmi, B.; Pande, K. R. (Journal of the Institute of Agriculture and Animal Science, 2018)
Hemato-biochemical profiles have been used widely to identify the health problems associated with productive and reproductive disorders. The objective of this study was to set up a baseline hematological and serum biochemical values. The study was carried out in 50 lactating cross bred Jersey cattle of Kaski district ranging in age from 3-7 years. Non-pregnant, lactating, apparently healthy and stall-fed cattle were selected for sampling and these animals were regularly dewormed and vaccinated against common diseases. All the hematological parameters were determined on the same day of collection using auto analyzer. The samples were also tested for blood protozoans (Anaplasma, Babesia, Theleria and Trypanosoma), using thin and thick smears. The serum samples were collected in a sterile vial for serum biochemical analysis and preserved at -200C until used for the assays. All the hematological parameters were within the normal range. However, 2% of the total animals tested appeared Theleria positive. Eosinophil and basophils were within the normal range suggesting that the deworming was effective and there was no allergic reaction. Mineral profile particularly glucose (11.75±0.87) was found significantly (P